2011
DOI: 10.1016/j.breast.2010.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship care after breast cancer treatment – Experiences and preferences of Australian women

Abstract: Follow-up care after breast cancer treatment is becoming more complex as it attempts to address the long-term needs of an increasing number of survivors. Workforce issues in oncology challenge the sustainability of current specialist-based care. This study explores survivors' experiences with follow-up care and attitudes to alternative models including a tailored survivorship care plan and involvement of primary care physicians and breast care nurses. Twenty women across Australia participated in semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
129
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(142 citation statements)
references
References 20 publications
11
129
2
Order By: Relevance
“…The authors also found that cancer survivors considered the care plan visit highly useful. The results are consistent with prior studies suggesting that in-person care plan visits are generally positive experiences for patients and can reduce anxiety and stress related to cancer (Jefford et al, 2011;Mayer et al, 2012).In contrast, the focus group studies indicated that patients believe that survivorship care plans would be valuable for improving communication among providers of care (Brennan et al, 2011;Kantsiper et al, 2009;Marbach & Griffie, 2011). The results suggest that current versions of survivorship care plans may not meet that goal.…”
supporting
confidence: 86%
“…The authors also found that cancer survivors considered the care plan visit highly useful. The results are consistent with prior studies suggesting that in-person care plan visits are generally positive experiences for patients and can reduce anxiety and stress related to cancer (Jefford et al, 2011;Mayer et al, 2012).In contrast, the focus group studies indicated that patients believe that survivorship care plans would be valuable for improving communication among providers of care (Brennan et al, 2011;Kantsiper et al, 2009;Marbach & Griffie, 2011). The results suggest that current versions of survivorship care plans may not meet that goal.…”
supporting
confidence: 86%
“…Poignant experiences of sa bcss highlighted how their experiences of post-treatment impacts matched with or varied from those of women in other cultural groups as they accessed health care in Canada. For the purposes of the present study, "unique" themes are those that emerged from health care experiences situated in the context of the sa women's meaning and understanding of disease and illness, possible migration, and acculturation experiences in light of social context and cultural expectations 20,[24][25][26][33][34][35][36][37][38] .…”
Section: Thematic Analysismentioning
confidence: 99%
“…Published literature indicates a growth in the development and implementation of SCPs internationally [3][4][5][6][7] but assessment of their impact on patient experience is rare. Van de Poll-Franse and colleagues have published their protocol of a randomized controlled trial (RCT) evaluating the impact of an SCP on gynaecological cancer survivors' satisfaction with information disclosure and care, quality of life, illness perception, and health care use [8] but there are no results to date.…”
mentioning
confidence: 99%